HR from the outside in six competencies for the future of human resources - Ulrich, David 1953- (McGraw-Hill, 2012)
"This definitive work on HR competencies provides ideas and tools that help HR professionals develop their career and make their organization effective." -Edward E. Lawler III, Professor, University of Southern California "This book is a crucial blueprint of what it takes to succeed. A must have for every HR professional." -Lynda Gratton, Professor, London Business School "One single concept changed the HR world forever: 'HR business partner' . Through consistent cycles of research and practical application, Dave and his team have produced and update the most comprehensive set of HR competencies ever." -Horacio Quiros, President, World Federation of People Management Associations "Packed with facts, evidence, and prescriptive advice. It is about being a business leader first, and an HR professional second." -Randy MacDonald, Senior Vice President, Human Resources, IBM Corporation "The concepts and competencies presented in this book provide HR leaders with new insights." -Gina Qiao, Senior Vice President, HR Lenovo "Powerful, relevant and timely! Defines "new HR" in a pragmatic way. This book is a must for leaders and HR folks who seek to create sustainable competitive advantage." -Satish Pradhan, Chief, Group Human Resources, Tata Sons Limited "You can't argue with the data! This book is a definitive and practical guide to learning the HR competencies for success." -John Lynch, Senior Vice President, HR, General Electric "A must read for any HR executive. This research-based competency model is particularly compelling because it is informed by the perspective of non-HR executives and stakeholders." -Sue Meisinger, Distinguished speaker and author, former CEO of SHRM "Read this book for a unique long-term perspective on where HR competencies have brought us and must take us in future." -John Boudreau, Professor, University of Southern California and Research Director, Center for Effective Organizations.
Includes bibliographical references and index. - Print version record
Keywords: Personnel management; Personnel Management; Personnel; Direction; Personeelsbeleid; Human recourse management